EFFECTIVENESS OF METHODS FOR TREATING INTRA-ARTICULAR FRACTURES OF THE DISTAL END OF THE THIGH BONE - Temurov Alisher Akmaljon ugli; Shamsiev Jasur Zafarovich; Ziyotov Lazizjon Izzatilla ugli; Nurumov Sarvar Yokub ugli; Musurmonov Urol Fozil ugli (Scholar Express Journals, 2024)
To study the comparative results and evaluate the effectiveness of osteosynthetic methods used in intra-articular fractures
Keywords: skeletal; evaluate; comparative